Vaccination in patients under monoclonal antibody treatment: an updated comprehensive review. (2nd August 2020) - Rivera-Izquierdo, Mario; Valero-Ubierna, Maria del Carmen; Nieto-Gómez, Pelayo; Martínez-Bellón, María Dolores; Fernández-Martínez, Nicolás Francisco; Barranco-Quintana, José Luis
ABSTRACT: Introduction: Monoclonal antibodies (mAbs) have become an increasing source of biological treatments. Clinicians should make an effort to update their knowledge on mechanisms of action, indications, and adverse events of these novel therapies. Most of them have immunosuppressive effects and, therefore, vaccination is indicated. Areas covered: vaccination of patients under mAbs therapies. Expert opinion: Recommendations on vaccination are still based on expert recommendations and have not been updated in recent years. Specific recommendations for each mAb have not been addressed in the current literature. The aim of this comprehensive review was to collect all the therapeutic mAbs approved up to 1 January 2020 and, based on previous recommendations and the pharmaceutical characteristics of each drug, to propose an updated guide with recommendations on vaccination. Influenza, sequential pneumococcal and Hepatitis B vaccination in patients with negative serology were the only consistent recommendations. Hepatitis A vaccination was proposed for mAbs with special hepatotoxic characteristics. Other vaccines are reviewed and discussed. Several non-immunosuppressive mAbs were detected and, therefore, vaccinations not recommended. We hope that this review can serve as a starting point for compiling updated vaccination recommendations and collecting all the therapeutic mAbs approved up to 2020.